ANJV-bijeenkomst t.g.v. vrijlating Koster. De Groot drukt Koster de hand. Links Teeboom-West - Meerendonk, Ben van,
ANJV-bijeenkomst t.g.v. vrijlating Koster. De Groot drukt Koster de hand. Links Teeboom-West.